(untitled) (JED (Jurnal Etika Demokrasi), 2025)
Sexual violence in higher education is a deeply rooted structural issue inadequately addressed solely through legal measures. This study investigates how members of an academic community construct their understanding of social sanctions as preventive tools against sexual violence on campus. Conducted at Universitas Muhammadiyah Makassar, the research employs a sequential explanatory mixed-method design, initially involving qualitative interviews with students, faculty, and institutional leaders. Subsequently, a quantitative survey was administered based on themes identified from the qualitative phase. Results indicate a broad consensus that social sanctions serve as effective normative controls, provided they are implemented consistently, fairly, and with community legitimacy. Quantitative analysis further confirms a significant relationship between perceptions of consistent sanction application by faculty and university leaders and the acceptance of social sanctions among the campus population. The study highlights the critical roles of institutional support, ethical education, and active community participation in fostering effective and sustainable violence prevention strategies. Practical recommendations emphasize integrating value-driven curricula and enhancing community involvement to build a socially responsive and equitable institutional environment.